Rancière’s Proust: A Rebirth of Aesthetics - Melaney, William (Res Cogitans, 2018)
Philosopher and literary theorist, Jacques Rancière, has argued that Marcel Proust’s work as a novelist enables us to understand how modern literature articulates and largely resolves a specifically aesthetic crisis. From Rancière’s standpoint, Proust shows us how the dominant conflict in nineteenth-century French literature was carried beyond a mere opposition and given a new aesthetic significance in the modern novel. In this paper, I will discuss Jacques Rancière’s attempt to assess Proust’s contribution to literature in the wake of the aesthetic tradition epitomized by Kant and Schiller. Crucial to this attempt is the deployment of aesthetics as a historical discourse that introduces the possibility of variation in relation to the real. More specifically, I will examine Rancière’s argument that metaphor in Proust’s work has the capacity to transform a sense of doubleness into a new understanding of the real.